Examination of Infrared Tomato Drying - Várkonyi, Zsombor; Sebesi, Viktória; Örvös, Mária (International Journal of Engineering and Management Sciences, 2020)
Tomato is a highly perishable food, thus preservation is required to meet the continuous market demand compared to the unbalanced yearly production peak. The aim of this paper is to show a detailed insight into infraradiation based drying process. Furthermore, to widen the possible usage range of a well-known approximation method for describing the temporal moisture variation in function of process parameters. The mass decrease of tomato slices was examined, in function of specific radiation power, heat source and sample distance, in forced and natural airflow. Based on the results dimensionless moisture ratio change over time was fitted as an exponential function, which may be used in industrial drying process optimization.